Asimetri Informasi Penyebab Underpricing IPO di Indonesia saat Pandemi Covid-19 - vivi ariyani (Jurnal Manajemen dan Keuangan, 2023)
This study aims to examine the factor that influence the underpricing of the Initial public offering (IPO), namely the Return on Assets and reputation of the underwriter. By using age, size, and trading volume as control variables on the level of underpricing of shares in companies conducting IPOs on the Indonesia Stock Exchange. The sample for this study was 112 companies for the 2020-2022 period using purposive sampling. From the results of data processing, it shows that the underwriter's reputation variable has a significant negative effect on the level of underpricing. This explains that the reputation of underwriters who are not included in the top 10 has an effect on increasing the underpricing of companies conducting IPOs. This is thought to cause information asymmetry between company management and investors. The results of this research can be taken into consideration by investors when deciding to invest in certain companies and government policy considerations when a company conducts an IPO on the stock exchange.